(3RhGd OhdI ESQGFjd (B:s (3MJejI bQBfjI (B/s - (3GdJejej, CSYO HjhV,s 1925- ((3YeGf (B- (3GdCQOf (B:s (3GdCgdjI ddfTQ hGdJhRjY ,s, 2006)
(3Cda GdTjN CSYO GdJejej gPG GdHMK YGe (B1974 (3cHMK Ydej, MjK Cf GdTjN jNGda cd GdeaSQjf GdbOGei aj JaSjQ BjGJ GdESQGA GdJj JJYdb HYdh OhdI ESQGFjd haSGOge aj GdCQV, hGSJfO GdTjN aj JaSjQg gPG Edi BjGJ GdbQBf GdCNQi, hEdi GdCMGOjK GdfHhjI hGddZI GdYQHjI, hGdhGbY GdJGQjNj, GdJj JDcO Cf JaSjQ Jdc GdBjGJ gh eG fYjTg Gdjhe hdjS eG bGd Yfg GdeaSQhf GdSGHbhf Cfg MOK bHd BdGa GdSfjf aj Ref fHhNP fUQ hGdBThQjjf hGdcdOGfjjf Ch GdaQS(B.s
(3JUeje GdZdGa (B: (3OGQ Gdaf ddJUeje ; GdUa GdVhFj (B: (3EjeGf RcQjG(B.s
Keywords: (3GdYQH hGdjghOs; (3GdbQBf hGdjghOjIs; (3adSWjfs -- (3aj GdbQBfs; (3ESQGFjds -- (3aj GdbQBfs